AMP affects intracellular Ca2+ signaling, migration, cytokine secretion and T cell priming capacity of dendritic cells. - Elisabeth Panther (Public Library of Science (PLoS), 2012)
The nucleotide adenosine-5'-monophosphate (AMP) can be released by various cell types and has been shown to elicit different cellular responses. In the extracellular space AMP is dephosphorylated to the nucleoside adenosine which can then bind to adenosine receptors. However, it has been shown that AMP can also activate A(1) and A(2a) receptors directly. Here we show that AMP is a potent modulator of mouse and human dendritic cell (DC) function. AMP increased intracellular Ca(2+) concentration in a time and dose dependent manner. Furthermore, AMP stimulated actin-polymerization in human DCs and induced migration of immature human and bone marrow derived mouse DCs, both via direct activation of A(1) receptors. AMP strongly inhibited secretion of TNF-α and IL-12p70, while it enhanced production of IL-10 both via activation of A(2a) receptors. Consequently, DCs matured in the presence of AMP and co-cultivated with naive CD4(+)CD45RA(+) T cells inhibited IFN-γ production whereas secretion of IL-5 and IL-13 was up-regulated. An enhancement of Th2-driven immune response could also be observed when OVA-pulsed murine DCs were pretreated with AMP prior to co-culture with OVA-transgenic naïve OTII T cells. An effect due to the enzymatic degradation of AMP to adenosine could be ruled out, as AMP still elicited migration and changes in cytokine secretion in bone-marrow derived DCs generated from CD73-deficient animals and in human DCs pretreated with the ecto-nucleotidase inhibitor 5'-(alpha,beta-methylene) diphosphate (APCP). Finally, the influence of contaminating adenosine could be excluded, as AMP admixed with adenosine desaminase (ADA) was still able to influence DC function. In summary our data show that AMP when present during maturation is a potent regulator of dendritic cell function and point out the role for AMP in the pathogenesis of inflammatory disorders.